Annual Plan 1984-85 Part-II Union Territory of Delhi - Planning Commission (Planning Commission, 1984)
Roods Development Outlay & Expenditure Annual Plan 19.84-85 Agencywise Breakuo Of Approved Outlay 84-85 Annual Plan 1984-85 Scheme-Wise Outlay And Expenditure Statement Indicating The Scheme-Wise Approved Outlay Under Annual Plan L984-85 Sectors- Co-Operation Schefie Wise Outlay And Expenditure Under Annual Plan 1984-85.
Planning Department Delhi Administration